A market entry strategy for a European company to the biomass based cogeneration industry for equipment and service suppliers in Thailand : a case study of standard biomass service, S.L., Spain - Thakur, Devashis; Johri, Lalit M.; Amoussou-Guenou, Roland; Lacrosse, Ludovic; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2004)
Biomass is one of the most important sources ofrenewable energy in Thailand and rest of the South East Asia since fuel wood is still the dominant source of energy in almost 50 percent of the region. Industries that rely on biomass as energy source are brick production, tobacco, lime production, smoking of rnbber sheet and fish mill production. The share of biomass in the Total Primary Energy Supply of the ten ASEAN Member Countries in 1998 was about 40 percent with Thailand's individual share being about 17%. With rising energy demand in Thailand where prima1y energy demand during 2006-2010 is forecasted to increase at an average rate of 4.6%, increasing importance given to Alternative Energy and a gradually liberalizing energy market, opportunities for small players in power production through alternative means like biomass are opening up. Hence it is has been interesting to study the changing nature of this industry and cogeneration market in particular as cogeneration is a very attractive option in terms of energy production in a very efficient way using non fossil fuel. Traditionally in this market the European companies have enjoyed a premium place for their proven technology and quality products. But recently, competition in this market has been complicated by the advent of many other players from EU, Japan and other Asian countries like China and India etc. Meanwhile many companies from traditionally developed countries are willing to make foray into this market because of gradual saturation of their home market and liberalization of the energy sector of the developing countries. In this complex dynamics, the case of a successful European company willing to make an entry into ASEAN region has been taken up for the research. To devise a foreign market entry strategy, a very careful analysis is needed of the external environment of the target country and the industry and a thorough study and critical internal examination of the company in terms of its resources & capabilities is mandato1y so that its core competency can be identified and a strategy can be formulated to compete in a sustainable basis in the countty where it aims to enter and operate. It has been identified that to enter and operate in the Thai and ASEAN market, the European company, Standard Biomass Service S.L. should rely on its core competency of Technology and should enter the market through strategic alliance route considering its limited resources in terms of finance and manpower and also the fact that it has got very little international business operation experience so far. The design of the strategic alliance has been done and an implementation process of the entry strategy have been developed and suggested to the company as an outcome of this research.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration. School of Management
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2004
Keywords: Biomass energy industries; Marketing -- Management